Evaluation of tacrolimus‐related CYP3A5 genotyping in China: Results from the First External Quality Assessment Exercise. Issue 8 (30th April 2018) - Lin, Guigao; Zhang, Xiao; Zhang, Kuo; Han, Yanxi; Tan, Liming; Li, Jinming
Abstract : Background: Tacrolimus is the most widely used immunosuppressant in solid organ transplant patients. The cytochrome P450 3A5 (CYP3A5) has been proved to be associated with tacrolimus dose requirement. Molecular detection for CYP3A5 genotyping is demanded for the optimization of treatments of tacrolimus. Methods: To achieve the consistency and accuracy of the testing results, the Chinese National Center for Clinical Laboratories (NCCL) organized a national external quality assessment(EQA) program to evaluate the performance of laboratories providing CYP3A5 genotyping. Ten validated DNA samples covering the common genetic polymorphisms of CYP3A5 were delivered to 33 voluntary laboratories, and their detecting results and clinical written reports were evaluated. Results: Thirty‐three datasets were received. The corresponding analytical sensitivity was 95.9% (285/297 challenges; 95% confidence interval: 93.0%‐97.9%), and the analytical specificity was 95.3% (346/363; 95% confidence interval: 92.6%‐97.2%). Thirty of the participating laboratories correctly identified the CYP3A5 allele status for all EQA samples. Three laboratories made genotyping errors, and 2 of them failed to detect any of the homozygotes such as *1/*1 and *3/*3 . Twenty‐eight CYP3A5*3 tests reports were submitted, but many reports showed a shortage of essential information. No reports fulfilled all the consensus recommendations for pharmacogenetic test result reporting. Conclusion: The EQA program highlighted the necessity for an improvement in the accuracy of genotyping for some of the laboratories and a greater education on the reporting of CYP3A5 genotyping results.